Epitope Mapping of Human HER2 Specific Mouse Monoclonal Antibodies Using Recombinant Extracellular Subdomains - Ghatar, Reza Hosseini (Asian Pac J Cancer Prev, 2017)
BACKGROUND: Human epidermal growth factor receptor 2 (HER2) is overexpressed in several human malignancies and numerous studies have indicated that it plays important roles in the development and maintenance of the malignant phenotype. Targeting of HER2 molecules with monoclonal antibodies (mAbs) is a promising therapeutic approach. However, anti-HER2 mAbs affect cancer cells differently, depending on the distinct epitopes which are the targets. METHODS: Reactivity of a panel of 8 mouse anti-HER2 mAbs was investigated by ELISA and Western blotting using different subdomains of the extracellular domain (ECD) of HER2. All subdomains, including I, II, III, IV, I+II, III+IV and full HER2-ECD were constructed and expressed in CHO cells. Cross-reactivity of the mAbs with other members of the human HER family and Cynomolgus HER2 was also studied by ELISA. The mAbs were also tested by immunohistochemistry (IHC) using HER2 positive breast cancer tissues. RESULTS: Our results demonstrated that 3 out of 8 mAbs detected conformational epitopes (1T0, 2A8 and 1B5), while 5 mAbs identified linear epitopes (1F2, 1H9, 4C7, 1H6 and 2A9). Three of the mAbs recognized subdomain I, one reacted with subdomain I+II, 2 recognized either subdomain III or IV and 2 recognized subdomain III+IV. However, none of our mAbs recognized the subdomain II alone. The mAbs displayed either inhibitory or stimulatory effects on HER2-overexpressing tumor cells and did not react with other members of the human HER family. The pattern of IHC results implied better reactivity of the mAbs recognizing linear epitopes. CONCLUSIONS: Our findings suggest that paired subdomains of HER2 are essential for mapping of mAbs recognizing conformational epitopes. Moreover, there seems to be no association between subdomain specificity and antitumor activity of our anti-HER2 mAbs.